Interplay Between the Autophagy-Lysosomal Pathway and the Ubiquitin-Proteasome System: A Target for Therapeutic Development in Alzheimer’s Disease - Bustamante, Hianara A.; González, Alexis E.; Cerda-Troncoso, Cristobal; Shaughnessy, Ronan; Otth, Carola; Soza, Andrea; Burgos, Patricia V. (Frontiers in Cellular Neuroscience, 2018)
Alzheimer´s disease (AD) is the most common cause of age-related dementia leading to severe irreversible cognitive decline and massive neurodegeneration. While therapeutic approaches for managing symptoms are available, AD currently has no cure. AD associates with a progressive decline of the two major catabolic pathways of eukaryotic cells — the autophagy-lysosomal pathway (ALP) and the ubiquitin-proteasome system (UPS) — that contributes to the accumulation of harmful molecules implicated in synaptic plasticity and long-term memory impairment. One protein recently highlighted as the earliest initiator of these disturbances is the amyloid precursor protein (APP) intracellular C-terminal membrane fragment  (CTF), a key toxic agent with deleterious effects on neuronal function that has become an important pathogenic factor for AD and a potential biomarker for AD patients. This review focuses on the involvement of regulatory molecules and specific post-translational modifications (PTMs) that operate in the UPS and ALP to control a single proteostasis network to achieve protein balance. We discuss how these aspects can contribute to the development of novel strategies to strengthen balance of key pathogenic proteins associated with AD.